An Exploratory Study of Cognitive Functioning and Psychological Well-Being in Middle-Aged Adults with Diabetes Mellitus - Halder, Susmita; Samajdar, Shinjini; Mahato, Akash Kumar (Journal of Social Health and Diabetes, 2020)
Background Diabetes mellitus is a chronic metabolic disorder characterized by increased level of blood sugar for a prolonged period of time. Apart from its impact on the bodily functions, the disorder has its own psychological consequences, commonly in terms of stress reaction, anxiety, and depression. Diabetes is also known to affect cognitive functions, but it is less studied in the Indian population and relatively ignored in the management plan. Discerning the cognitive functions in middle-aged adults diagnosed with diabetes can give valuable insight into comprehensive management of the disorder. With this background, the study attempted to explore the cognitive functioning and psychological well-being of middle-aged adults with diabetes and compared with healthy individuals.Methods A total of 30 middle-aged adults of both sexes diagnosed with diabetes type 2 were undertaken for the study and compared with 30 healthy adults regarding measures of cognitive functioning and psychological well-being. The measures were also explored for relationship if any with illness duration.Results Middle-aged adults with diabetes differed significantly in terms of response inhibition and processing speed compared with healthy controls. The groups significantly differed on subjective Psychological well-being in terms of self-control, anxiety and depression, and vitality. Duration of illness was found to be related to anxiety symptoms.Conclusion Diabetes affects response inhibition and processing speed in middle-aged adults. Assessing and addressing impairment in cognitive functions is recommended for a comprehensive management of diabetes in middle-aged adults.
Keywords: diabetes; middle–aged adults; cognitive functioning; well-being